2022
DOI: 10.3389/fcimb.2022.1038253
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies relationships between nosocomial pathogens associated to preterm infants and lactic acid bacteria in dual-species biofilms

Abstract: The nasogastric enteral feeding tubes (NEFTs) used to feed preterm infants are commonly colonized by bacteria with the ability to form complex biofilms in their inner surfaces. Among them, staphylococci (mainly Staphylococcus epidermidis and Staphylococcus aureus) and some species belonging to the Family Enterobacteriaceae are of special concern since they can cause nosocomial infections in this population. NETF-associated biofilms can also include lactic acid bacteria (LAB), with the ability to compete with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…NEFTs may also be the source of lactic acid bacteria, which may arise from inoculating OMM through these devices, with potential to modulate the process of NEFT colonization. As an example, in a previous work we showed that Ligilactobacillus salivarius 20SNG3 was effective in modulating the ability of biofilm formation of NEFT-isolated K. pneumoniae and S. marcescens strains ( 83 ).…”
Section: Discussionmentioning
confidence: 95%
“…NEFTs may also be the source of lactic acid bacteria, which may arise from inoculating OMM through these devices, with potential to modulate the process of NEFT colonization. As an example, in a previous work we showed that Ligilactobacillus salivarius 20SNG3 was effective in modulating the ability of biofilm formation of NEFT-isolated K. pneumoniae and S. marcescens strains ( 83 ).…”
Section: Discussionmentioning
confidence: 95%
“…NEFTs may also be the source of lactic acid bacteria, which may arise from inoculating OMM through these devices, with potential to modulate the process of NEFT colonization. As an example, in a previous work we showed that Ligilactobacillus salivarius 20SNG3 was effective in modulating the ability of biofilm formation of NEFT-isolated K. pneumoniae and S. marcescens strains (83).…”
Section: Discussionmentioning
confidence: 92%